PSYCHOLOGICAL CHANGES IN WOMEN WITH CERVICAL CANCER: A SYSTEMATIC REVIEW - Widiasih, Restuning; Trisyani, Mira; Nurdani, Gema Riksa; Handayani, Leni Riksa; Hariyawinata, Nanda Riksa; Pitriani, Rita Riksa; Nurrizkiani, Rizka Riksa; Akbar, Ruli Nur; Lestari, Silvani S; Ramdani, Sucia S (Journal of Maternity Care and Reproductive Health, 2024)
Cancer has become the leading cause of death in recent years. The incidence of cervical cancer in Indonesia is the second highest after breast cancer. Research on psychological changes is minimal, and there is limited information on the exposure of psychological changes in women with cervical cancer. Objectives to determine the presence of psychological changes in women with cervical cancer based on literature analysis.  The method used was a systematic review with article selection using the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) guidelines. The article search results obtained 36 articles from 5 databases, namely PubMed, Science Direct, Scopus, Research Gate, and CINAHL. The 36 articles were evaluated using JBI critical appraisal, and ten articles were obtained that met the inclusion criteria; the final seven articles could be further analysed. Results: the results of the literature review found that there are psychological changes in women with cervical cancer. Combining psychological approaches and empowering the patient's potential in dealing with changes is expected to reduce psychological problems in women with cervical cancer. Conclusions: there are psychological changes in women with cervical cancer. Combining a psychological approach and empowering the patient's potential in dealing with change is expected to reduce psychological problems in women with cervical cancer. Therefore, patients with cervical cancer need emotional support and information to survive. Suggestions for further research can be conducted with a more significant number of samples with research that explains the mechanism of action or intervention.